The Plant Microbiome and Native Plant Restoration: The Example of Native Mycorrhizal Fungi. (14th November 2018) - Koziol, Liz; Schultz, Peggy A; House, Geoffrey L; Bauer, Jonathan T; Middleton, Elizabeth L; Bever, James D
Abstract: Ecological restoration efforts can increase the diversity and function of degraded areas. However, current restoration practices cannot typically reestablish the full diversity and species composition of remnant plant communities. We present evidence that restoration quality can be improved by reintroducing key organisms from the native plant microbiome. In particular, root symbionts called arbuscular mycorrhizal fungi are crucial in shaping grassland communities, but are sensitive to anthropogenic disturbance, which may pose a problem for grassland restoration. In the present article, we highlight the conceptual motivation and empirical evidence evaluating native mycorrhizal fungi, as opposed to commercial fungi. Reintroduction of the native microbiome and native mycorrhizal fungi improves plant diversity, accelerates succession, and increases the establishment of plants that are often missing from restored communities. The example of mycorrhizal fungi serves to illustrate the value of a more holistic view of plant communities and restoration that embraces the intricacies and dynamics of native microbial communities.